2004
DOI: 10.1001/archpedi.158.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Urban Children's Perceptions of Violence

Abstract: Future investigators measuring the effect of violence-prevention activities on preteen children should be aware that their definition of violence may differ from that of young children and should be cognizant of potential sex differences, especially around the topic of intimate-partner violence. Those designing violence-prevention programs for children should consider engaging adult family members as well because children usually turn to them for safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…13,28 Sheehan et al found that some urban youth did not trust the police and perceived them as violent. 29 Present findings also stress the paramount role the school environment plays in youth aggression and violent behavior. While some teachers and principals were able to mitigate aggression and violence, others expressed aggression and used violence towards students.…”
Section: Discussionmentioning
confidence: 52%
“…13,28 Sheehan et al found that some urban youth did not trust the police and perceived them as violent. 29 Present findings also stress the paramount role the school environment plays in youth aggression and violent behavior. While some teachers and principals were able to mitigate aggression and violence, others expressed aggression and used violence towards students.…”
Section: Discussionmentioning
confidence: 52%
“…A recent study by Sheehan and colleagues suggests that preadolescent urban youth look to trusted adults to help keep them safe from violence. 15 Our findings indicate that, with age, youths may come to trust the adults in their lives less, and develop their own strategies for staying safe. When available, peers with similar life experiences may inform those strategies.…”
Section: Discussionmentioning
confidence: 72%
“…What has to be determined are adolescent perceptions concerning what might constitute a weapon, the lethality of any weapons being carried, and the context in which they might be used. A recent focus group-based study 13 of perceptions of violence among urban children might act as a good model for further research on this topic in NZ.…”
Section: Discussionmentioning
confidence: 99%